Iron-dependent reconfiguration of the proteome underlies the intracellular lifestyle of Brucella abortus - Roset, Mara Sabrina (2017)
Brucella ssp. is a facultative intracellular pathogen that causes brucellosis, a worldwide zoonosis that affects a wide range of mammals including humans. A critical step for the establishment of a successful Brucella infection is its ability to survive within macrophages. To further understand the mechanisms that Brucella utilizes to adapt to an intracellular lifestyle, a differential proteomic study was performed for the identification of intracellular modulated proteins. Our results demonstrated that at 48 hours post-infection Brucella adjusts its metabolism in order to survive intracellularly by modulating central carbon metabolism. Remarkably, low iron concentration is likely the dominant trigger for reprogramming the protein expression profile. Up-regulation of proteins dedicated to reduce the concentration of reactive oxygen species, protein chaperones that prevent misfolding of proteins, and proteases that degrade toxic protein aggregates, suggest that Brucella protects itself from damage likely due to oxidative burst. This proteomic analysis of B. abortus provides novel insights into the mechanisms utilized by Brucella to establish an intracellular persistent infection and will aid in the development of new control strategies and novel targets for antimicrobial therapy.